EPIDEMIOLOGY OF BURN TRAUMA IN METROPOLIS - Yu. R. Yunusova; S. G. Shapovalov; E. P. Sukhoparova; E. I. Besedina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The analysis of the structure and comparative assessment of injuries and deaths in fires in Moscow and the Russian Federation for 2011-2015 was performed. The number of victims in the fires in Moscow during 5 years – 4.084 persons. The part of deaths is 25 %. The number of deaths per 100 fires on average is 35.1 per year, what is 5 times more than in Russia as a whole. However, since 2011 by 2015 the number of deaths in fires decreased by 7.2 %. Convincing data during 5 years on reducing the risk for a person to die in a fire (R2sm) was not received. The indicator in Moscow fluctuates in the direction of increase, while in the Russian Federation it remains at a high level. The same applies to the risk for a person to get injured in a fire and its dangerous factors (R2tr). For 5 years in Russia the risk indicator has grown, but in Moscow it remained at the same level. Individual risk for a person to die in a fire and its dangerous factors (R3sm), as well as individual risk for a person to get injured in a fire and its dangerous factors (R3tr) in Russia decreased, and in Moscow remained practically at the same level as testifies that during this period of time there were no positive shifts.